Population, Exchange Rate and Foreign Direct Investment on Openness Trade in Interregional (RCEP): Panel Dynamic - GMM - Devi Aria Nanda; Fahrizal Taufiqqurrachman (Trunojoyo University of Madura, 2025)
This study aims to determine the effect of population, exchange rates, and investment on international trade in countries that are members of RCEP. With the approach of dynamic panel data analysis method with 15 countries namely ASEAN, Japan, South Korea, Australia, China, and New Zealand. in 2012-2022, which sourced data from the World Development Indicator (WDI) World Bank with the generalized moment method (GMM). The results showed that the FD-GMM assumption did not meet 3 estimates (arellano-bond test, sargan test, and model specification test) then continued with the SYS-GMM assumption which successfully met 3 estimates, then the regression results of the SYS-GMM model will be used in the discussion. The results of the analysis show that an increase in population will increase trade by 0.149068%. Likewise, an increase in the exchange rate will also increase trade by 0.0795209%. And if there is an increase in investment, it will increase trade by 0.0111297%. This shows that population, exchange rates, and investment have a positive and significant effect on international trade. From the results of this study, it is hoped that the government can provide appropriate policies so that the policies implemented can be realized and the government can also increase population and labor, policies to increase economic competitiveness, and policies to increase economic stability, to increase trade.